Scrimer: designing primers from transcriptome data. (31st March 2015) - Mořkovský, Libor; Pačes, Jan; Rídl, Jakub; Reifová, Radka
Abstract With the rise of next‐generation sequencing methods, it has become increasingly possible to obtain genomewide sequence data even for nonmodel species. Such data are often used for the development of single nucleotide polymorphism (SNP) markers, which can subsequently be screened in a larger population sample using a variety of genotyping techniques. Many of these techniques require appropriate locus‐specific PCR and genotyping primers. Currently, there is no publicly available software for the automated design of suitable PCR and genotyping primers from next‐generation sequence data. Here we present a pipeline called Scrimer that automates multiple steps, including adaptor removal, read mapping, selection of SNPs and multiple primer design from transcriptome data. The designed primers can be used in conjunction with several widely used genotyping methods such as SNaPshot or MALDI‐TOF genotyping. Scrimer is composed of several reusable modules and an interactive bash workflow that connects these modules. Even the basic steps are presented, so the workflow can be executed in a step‐by‐step manner. The use of standard formats throughout the pipeline allows data from various sources to be plugged in, as well as easy inspection of intermediate results with visualization tools of the user's choice.